2006
DOI: 10.1242/dev.02600
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFI is required for the formation of commissural projections in the forebrain by regulating axonal growth

Abstract: The transcription factor COUP-TFI (NR2F1), an orphan member of the nuclear receptor superfamily, is an important regulator of neurogenesis, cellular differentiation and cell migration. In the forebrain, COUP-TFI controls the connectivity between thalamus and cortex and neuronal tangential migration in the basal telencephalon. Here, we show that COUP-TFI is required for proper axonal growth and guidance of all major forebrain commissures. Fibres of the corpus callosum, the hippocampal commissure and the anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 51 publications
4
82
0
Order By: Relevance
“…In this study, we found that in the absence of COUP-TFI (Nr2f1 -Mouse Genome Informatics), a transcription factor crucial for corticogenesis and arealization (Armentano et al, 2006;Armentano et al, 2007;Tomassy et al, 2010), Rnd2 expression is abnormally high in the SVZ and IZ during glia-guided radial migration. As a consequence, a greater number of MSCs are stalled in the IZ and BSC migration to the CP is impaired.…”
Section: Introductionmentioning
confidence: 86%
“…In this study, we found that in the absence of COUP-TFI (Nr2f1 -Mouse Genome Informatics), a transcription factor crucial for corticogenesis and arealization (Armentano et al, 2006;Armentano et al, 2007;Tomassy et al, 2010), Rnd2 expression is abnormally high in the SVZ and IZ during glia-guided radial migration. As a consequence, a greater number of MSCs are stalled in the IZ and BSC migration to the CP is impaired.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, in the absence of COUP-TFI function, this repression is released and an excess of PVϩ interneurons is produced. Since COUP-TFI is expressed in the MGE from E10.5 to E12.5 (Armentano et al, 2006(Armentano et al, , 2007this study), and production of PVϩ interneurons occurs from E9.5 to E15.5 (Miyoshi et al, 2007), it is reasonable to assume that presumptive PVϩ cells express COUP-TFI while proliferating and that COUP-TFI normally controls early SVZ progenitor divisions during generation of PVϩ interneurons.…”
Section: Coup-tfi Controls the Balance Between Mge-and Cge-derived Inmentioning
confidence: 92%
“…An expanded SVZ observed in the COUP-TF single and double conditional mutants may directly result from the accumulation of DCX+ immature neuroblasts, and CR+ and NeuN+ mature neurons. However, because most excitatory projection neurons in the neocortex also lost COUP-TFI expression, which can lead to the changes in cortical area patterning and altered axonal projections (Zhou et al, 1999(Zhou et al, , 2001Armentano et al, 2006Armentano et al, , 2007Faedo et al, 2008;Borello et al, 2014), these phenotypes may also indirectly result in an expanded SVZ.…”
Section: Redundant Functions Of Coup-tfi and Coup-tfiimentioning
confidence: 99%